Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1096/fj.11-186817
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle‐associated nucleic acids mediate trait dominance in cancer

Abstract: Drug resistance is a major cause of cancer treatment failure, with multidrug resistance (MDR) being the most serious, whereby cancer cells display cross-resistance to structurally and functionally unrelated drugs. MDR is caused by overexpression of the efflux transporters P-glycoprotein (P-gp) and multidrug resistance-associated protein 1 (MRP1). These transporters act to maintain sublethal intracellular drug concentrations within the cancer cell, making the population treatment unresponsive. Recently, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 43 publications
(60 reference statements)
9
111
0
Order By: Relevance
“…While the antigens on the surface of MVs can resemble those of their parental cells [48] , many studies have shown that MVs contain a more unique cargo than the parental cells [8,10,11,17,49] . The microparticles shed from drug-resistant cancer cells are able to spread the cell surface P-glycoprotein (P-gp) to the drug-sensitive recipient cells [11] , and cancer cells harboring oncogenic EGFR can export this receptor in MVs, leading to transformation-like changes in the adjacent tumor cells and endothelial cells [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the antigens on the surface of MVs can resemble those of their parental cells [48] , many studies have shown that MVs contain a more unique cargo than the parental cells [8,10,11,17,49] . The microparticles shed from drug-resistant cancer cells are able to spread the cell surface P-glycoprotein (P-gp) to the drug-sensitive recipient cells [11] , and cancer cells harboring oncogenic EGFR can export this receptor in MVs, leading to transformation-like changes in the adjacent tumor cells and endothelial cells [9] .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have reported that tumor cellderived MVs (TMVs) reflect the special potential of tumor cells for the expansion of the tumor, independently from cell to cell contact [14,15] . Recently, a growing body of evidence suggests that TMVs contain a selective enrichment of a discrete set of cellular molecules that can be transferred into the target cells [16][17][18][19] . Interestingly, Thompson et al [20] recently confirmed that exosomes, which are a different kind of vesicle with different origins, sizes and content, are secreted by myeloma cells, and emerging evidence has shown that TMVs act as novel angiogenic mediators and can stimulate angiogenesis in tumors [14,19,[21][22][23] ; however, it is not clear whether MVs can be secreted by myeloma cells (MM-MVs).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has since been shown to occur in vivo , whereby these microparticles transfer resistance proteins deep within the tumor core within 24 hours of MP exposure. This process also serves to "retemplate" the transcriptional landscape of recipient cells and in doing so results in the selective dominance of deleterious traits within the cancer cell population (Jaiswal et al, 2012a). Furthermore, in addition to the transfer of resistance proteins mediating MDR, these microparticles effectively sequester anticancer drugs and reduce the available free drug concentration available to a tumor mass, hence constituting a parallel resistance pathway (Gong et al, 2012).…”
Section: Microparticles As Novel Therapeutic Targets For the Preventimentioning
confidence: 99%
“…This transfer resulted in the acquisition, by the recipient cells, of the drug resistant characteristics of the donor cells. 153,160,161 In a recent study, the authors analysed the molecular basis for the acquired traits, looking for some miRs which had previously been reported 73,106,129,130,144 (and described above) as enhancers of P-gp expression in drug resistant cancer cells (miR-27a and miR-451). They demonstrated that the transfer of transcripts and miRs through microvesicles plays an important role in conferring MDR by "retemplating" recipient cells in order to reflect the donor cell (P-gp overexpressed) phenotype.…”
Section: P-gp and The Micrornas Involved In Its Regulation May Be Prementioning
confidence: 99%